Dual dielectric grating-assisted enhancement of Goos-Hänchen shift in monolayer graphene. (1st August 2022) - Ma, Shanshan; Zhu, Xiaojun; Lu, Delian; Da, Haixia
Abstract: Recently, the dielectric gratings have been used in enhancing the Goos-Hänchen (GH) shifts of monolayer graphene. However, many of these structures are limited within single dielectric grating. Dual dielectric gratings are compelling candidates for the manipulation of the light–matter interaction owing to their flexible degree of freedom in geometrical parameters. Here, we present the GH shift of the reflected wave in the dual dielectric grating layers by using rigorous coupled-wave analysis and stationary phase method, where a monolayer graphene is placed over the lower dielectric grating layer and the upper and lower dielectric grating layers have different filling factors. It is found that a relatively large GH shift, with amplitude up to more than 8000 times of the incident wavelength, can be achieved in the dual dielectric grating layers with monolayer graphene due to the joint excitation of the guided mode resonance in both the upper and lower dielectric grating layers. In addition, we can control the magnitude and position of GH shifts by changing chemical potential of monolayer graphene and the geometrical parameters of the dual dielectric grating layers. Our work opens a possibility for the improvement of the GH shift in the combined structure with the dual dielectric grating layers and the two-dimensional layered structure, which might enable the novel optoelectronic devices.